Family members and health professionals' perspectives on future life planning of ageing people with Down syndrome: a qualitative study. Issue 24 (20th November 2018) - Covelli, Venusia; Raggi, Alberto; Paganelli, Chiara; Leonardi, Matilde
Abstract: Objectives: To address the way in which primary caregivers of people over 45 with Down syndrome describe daily life activities and context and foresee their future. Methods: Thirteen family members and 15 health professionals participated to four focus groups. Meaningful concepts were identified and linked to the International Classification of Functioning, Disability and Health using established linking rules. Results: A total of 258 relevant concepts were identified and linked to 75 categories of the classification: 38 were from activity and participation and 17 from environmental factors domains. The most commonly reported issues were mental functions (b117-intellectual functions and b152-emotional functions), community life activities (d910-community life and d920-recreation and leisure) and environmental factors (e310-support of immediate family, e355-support from health professionals and e555-associations and organizational services). Conclusions: Information on the daily life and health of ageing people with Down syndrome is important to plan social and health care interventions tailored to deal with problems that they may encounter in older age. Considering the interaction between health and environment and maintaining a continuity of daily routines were reported as the most relevant topics for managing daily lives of persons with Down syndrome in older ages. Implications for rehabilitation: Pay more attention to the interaction between environmental factors and health condition in ageing people with Down syndrome. Information about the life contest are important in order to plan present and future social–health care interventions. Future planning for people with Down syndrome is a great concern for family members.